INVESTIGATION OF ELECTRODEPOSITED Ni-TiAlN COMPOSITE FILM - Esmar Budi; Iwan Sugihartono; Agus Setyo Budi; Setia Budi; Alief Restu; Adhyatma Alamsyah; Ade Lina Permata; Muarief Muarief (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2014)
Electrodeposition of Ni-based composite films on metal is subjected to improve its wear and corrosion resistances. Hard nitride compound particles commonly are added into Ni matrix to enhance the composite film properties. The compound has excelent properties especally in mechanical and corrosion resistances. Electrodeposited Ni-TiAlN composite film on tungsten carbide rod as substrate has been investigated. Amount of 2 gr/liter of TiN and AlN powders were added into the electrolyte solution that consists of 0.38 M Ni2SO4.6H2O, 0.17 M NiCl2.6H2O and 0.49 M H3BO3. The experiment was performed at electrodeposition current of 3.5 and 40 mA for about 10 minutes. The results show that the composite film morphology is refined as increasing of electrodeposition current. Keywords: Ni-TiAlN composite film, electrodeposition, tungsten carbide, electrolyte solution.